Analysis of teamwork in officiating in basketball - Smid, P. (Journal of Human Sport & Exercise, 2015)
The aim of this paper is to characterise the role, activity and participation of the referees in games with a focus to basketball games. The author generally discusses these issues analysing changes in referees teamwork during the last three years, He presents referees´ individual positions on the basketball court (lead, centre, trail), places of their competences, duties and responsibilities. The method of study was direct observation of 45 basketball games during seasons 2012-2014 in mens basketball of the Mattoni National Basketball League in the Czech Republic. The author compares the basic three positions according to the criteria of the area on the basketball court, referees´position and time in the game in relation to the players´ personal fouls. Results of the research show significant changes in the participating basketball referees during the game, indicating the most common problems in referees´ teamwork and suggestions on how to improve this work.